Non-alcoholic cirrhosis and heart rate variability: A systematic mini-review - Do Amaral, Joice Anaize Tonon; Salatini, Renata; Arab, Claudia; Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP]; Monteiro, Carlos B.M.; Tannuri, Uenis; Tannuri, Ana Cristina Aoun (MDPI, 2020)
Background and Objectives: Cirrhosis is a liver disease that causes about one million deaths annually worldwide. The estimated cirrhosis prevalence ranges from 4.5–9.5% in the general population. Up to 40% of cirrhotic patients are asymptomatic and may be diagnosed late. Studies have described the importance of the functions of the liver and autonomic nervous system (ANS) and their relationship. There is limited information available on non-alcoholic cirrhosis and heart rate variability (HRV), which is a measure of the ANS. This study aimed to evaluate cardiac autonomic modulation through HRV in non-alcoholic cirrhosis individuals reported in previous observational and clinical trial studies. Materials and Methods: We performed a systematic review according to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) statement using the Medline, Scopus, and Web of Science electronic databases. Five studies were identified and reviewed. Results: HRV was decreased in patients with non-alcoholic cirrhosis, even in the first stage. Conclusions: HRV could be used as a complementary method to improve both the diagnosis and prognosis of non-alcoholic cirrhosis.
Keywords: Autonomic nervous system disorders; End stage liver disease; Heart rate variability; Liver cirrhosis